2006
DOI: 10.1037/0278-7393.32.4.816
|View full text |Cite
|
Sign up to set email alerts
|

Assessing text representations with recognition: The interaction of domain knowledge and text coherence.

Abstract: Readers construct at least 2 interrelated mental representations when they comprehend a text: a textbase and a situation model. Two experiments were conducted with recognition memory to examine how domain knowledge and text coherence influence readers' textbase and situation-model representations. In Experiment 1, participants made remember-know judgments to text ideas. Knowledge and coherence interacted to influence remember judgments differently than know judgments. In Experiment 2, the authors used the proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 44 publications
(83 reference statements)
1
29
0
Order By: Relevance
“…In this regard, the association of recollection with the elaborative and inferential aspects of stimulus encoding (Long, Wilson, Hurley, & Prat, 2006;Mandler, 1980;Yonelinas, 2002) has stemmed from the application of dual-process analyses. However, the phantom recollection process is itself strongly associated with highly inferential representations, such as situation models.…”
Section: Recollectionmentioning
confidence: 99%
“…In this regard, the association of recollection with the elaborative and inferential aspects of stimulus encoding (Long, Wilson, Hurley, & Prat, 2006;Mandler, 1980;Yonelinas, 2002) has stemmed from the application of dual-process analyses. However, the phantom recollection process is itself strongly associated with highly inferential representations, such as situation models.…”
Section: Recollectionmentioning
confidence: 99%
“…There was a tendency of the high knowledge readers to attain the best results, taking advantage of a minimally cohesive text, but not in the diagram task, where they benefited from the most cohesive text. Long, Wilson, Hurley, and Prat (2006) investigated the influence of knowledge about the topic of a story and cohesion on readers' text representations using recognition memory. They found that high-knowledge readers had a better recall with the low-cohesion texts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Long and her colleagues have argued that the recollection and familiarity estimates can be used to examine the nature of readers’ text representations (Long & Prat, 2002; Long, Prat, Johns, Morris, & Jonathan, 2008; Long, Wilson, Hurley, & Prat, 2006). According to dual-process models, recollection increases when studied items are elaborated, that is, when semantic and conceptual processing yields relations among items.…”
Section: Recollection Familiarity and Readers’ Text Representationsmentioning
confidence: 99%